Wykorzystanie funduszy unijnych na inwestycje ochronny środowiska w latach 2004-2006 w świetle realizacji polityki spójności - Kryk, Barbara (Using European Union funds for investments in the environmental protection in the period of 2004-2006 in the light of the realization of the cohesion policy, 2007)
The first period is passing, to which it has been planned using European Union funds. There already exist reliable sets of data and the information enabling to determine, what for and on what level these funds have been used. Using union funds for the environmental protection is one of morę important problems. On that account in the article are presented: conclusions from current using European Union funds for investments in the environmental protection, the place and the role of environmental investments in the realization of the European cohesion policy in the light of the document National Strategie Frames of References.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 470-479